The language of Art : inquiry-based studio practices in early childhood settings - Day, Alison (London : Routledge, 2011)
This volume explains how to set up a properly run, effective and enjoyable drama club in your school. It contains lesson plans and practical exercises for running a drama club for a whole school year - three 11-week termly sessions, each one built around developing the social skills children need to become effective and positive communicators.
Keywords: Drama -- Study and teaching (Elementary) -- Great Britain; Drama in education -- Great Britain